Jaminan Kesehatan Nasional (JKN) dan Kepuasan Layanan Kesehatan Reproduksi National Health Insurance and Reproductive Health Service Satisfaction - Dwi Agustanti; Anita Anita; Purwati Purwati; Kodri Kodri (JURNAL KEPERAWATAN RAFLESIA, 2022)
Women's health problems in Indonesia are still in the spotlight and concern. Maternal mortality did not show a decline but instead increased to 305 deaths per 100,000 live births. Since the COVID-19 outbreak was declared a national disaster on February 29, 2020, the government recommended that all health services focus on and prioritize handling COVID-19 and other health problems. others that are considered medical emergencies, thus changing the priority of health services reduces Sexual and Reproductive Health (KSR) services. This study aimed to determine the relationship of the National Health Insurance (JKN) with satisfaction with reproductive health services. This study used a quantitative method with a cross-sectional design. The sample were 257 respondents who meet the criteria, namely aged between 20 - 50 years and use women's health services (reproductive) in health facilities in Bandar Lampung City. The test used univariate with frequency distribution and bivariate test with Chi Square. The results found that more respondents used JKN in women's health services, 184 people (71.6%), more respondents said they were satisfied with women's health services, 129 people ( 50.2%). There was no relationship between the use of JKN with women's health service satisfaction (p value 0.891). Suggestions for the Poltekkes institution to increase participation in the coverage of JKN participation in the community, especially women in the city of Bandar Lampung.